2021
DOI: 10.20473/jbe.v9i12021.88-95
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Hypertension, Obesity, and Smoking as Risk Factors for Chronic Kidney Disease in Productive Age

Abstract: Background: Based on the Indonesia basic health research report in 2018, the prevalence of chronic kidney disease (CKD) in the productive age group in Indonesia had increased from the previous year, to 1.97%. This condition can cause various complications that contribute to the high morbidity, which affects quality of life and productivity, so risk factors for CKD need to be understood to prevent the occurrence of the disease. Purpose: This study aimed to analyze the risk factors associated with CKD in the Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…13 Moreover, we also found a large number of patients had a history of diabetes mellitus (75%) with an average HbA1c level of 6.85AE1.67%. This is in accordance with a study by Sinusi and Hargono (2021) according to data from the Indonesian Family Life Survey 5 (IFLS-5), which showed that hypertension and diabetes mellitus are the primary risk factors for CKD. 14 Uncontrolled hypertension is a risk factor of arteriolar nephrosclerosis, a vascular injury in the preglomerular arterioles that leads to glomerular ischemia, 15 whereas a high level of blood glucose will impair the insulin signaling pathway in the glomerulus of the kidneys, which leads to proapoptotic environment.…”
Section: History Of Hypertension and Diabetes Mellitussupporting
confidence: 92%
“…13 Moreover, we also found a large number of patients had a history of diabetes mellitus (75%) with an average HbA1c level of 6.85AE1.67%. This is in accordance with a study by Sinusi and Hargono (2021) according to data from the Indonesian Family Life Survey 5 (IFLS-5), which showed that hypertension and diabetes mellitus are the primary risk factors for CKD. 14 Uncontrolled hypertension is a risk factor of arteriolar nephrosclerosis, a vascular injury in the preglomerular arterioles that leads to glomerular ischemia, 15 whereas a high level of blood glucose will impair the insulin signaling pathway in the glomerulus of the kidneys, which leads to proapoptotic environment.…”
Section: History Of Hypertension and Diabetes Mellitussupporting
confidence: 92%
“…Other comorbidities such as hypertension and diabetes mellitus are factors that contribute to the level of difficulty experienced by family caregivers ( Bestari, 2017 ). Poor lifestyle factors such as obesity and smoking make it difficult for family caregivers to care for patients with CKD ( Sinusi & Hargono, 2021 ). The patient's condition, which hinders the undergoing dialysis process, greatly aggravates the treatment and affects the physical capacity of family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous Studies found that smoking became a risk factor the diseases such as cardiovascular disease, stroke, and chronic kidney disease at a productive age. [13][14][15] Prevention approaches have included peer education, banning smoking in public areas, restricting cigarette advertising, and increase the tax on cigarette. However, the number of adolescent smokers is still high.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Previous Studies found that smoking became a risk factor the diseases such as cardiovascular disease, stroke, and chronic kidney disease at a productive age. 13 15 …”
Section: Introductionmentioning
confidence: 99%